The role of corporate social investments on teacher development in schools : a research study on mathematics initiatives in public schools supported by the Epoch and Optima Trusts. - Madisha, Edwin Mohlopi (My University, 2013)
Improving learner achievement and performance remains a global challenge for many governments, especially in developing countries. Countries spend a sizeable percentage of their national budgets on education with the hope to achieve desired learner outcomes. In South Africa, legislation has made provision for companies to contribute 1% of their net profit towards social development, including education. It is within this background, that the Epoch and Optima Trusts invested significant sums of money to improve the quality of maths results in secondary schools. The study investigates school level activities to ascertain whether and to what extent these may be implicated in improved teaching practices leading to improved performance. We interrogate the assumption commonly stated in the school effectiveness literature that teaching practices in schools are stimulated and facilitated by activities occurring at that school level. The literature is inclined to the view that whatever happens in classrooms is influenced by school level instructional leadership practices, professional development of teachers and the maintenance of internal accountability measures. We preferred to make use of case study research method in order to explore teacher practices in schools because the purpose is to understand behavioural detail and impact mechanisms. A matched pairs sampling technique was used to select four schools from a population of 78 public schools which were continually supported by the Trusts over a period of two years. One pair was classified as former Model C schools (one high performing and one low performing), while the other pair consisted of two former Department of Education and Training schools (one high performing and one low performing). This design reduces the socio-economic and cultural differences between the two schools in each pair. A framework was derived from the literature to guide the collection and analysis of data. The framework commences with the three categories of school level practices, disaggregated into eight specific activities. A set of indicators was then formulated to assess the degree to which each of the specific practices was present in schools. Collective responses of four interviewees at each school were rated and triangulated during this process. Given the nature and the size of the sample, we cannot generalise on the basis of four case studies. However, the value of this report is that we have developed:  a scheme for describing and analysing school-level practices that may facilitate and optimise teaching and learning, and  a set of hypotheses for accounting for improved school performance. In conclusion, we inferred that schools that institutionalised some practices and systems as identified were able to increase and maintain the number of quality passes in mathematics and as such, meeting the objectives of the donors. The factors which appear to hold the most potential for optimising performance in the two high SES former Model C schools are collegial practices on curriculum, pedagogy and assessment. In the two low SES former DET schools performance advantage seems to be enhanced by the systematic use of assessment data and by an increased sense of intrinsic motivation on the part of teachers.
Keywords: Mathematics--Study and teaching (Secondary)--South Africa.; Mathematics teachers--South Africa.; Social responsibility of business--South Africa.